Challenges in Connecting The Elements of Sectoral System of Innovation for Developing Electric Vehicle Industry in Indonesia - Ariyani, Luthfina; Dinaseviani, Anggini; Rosadi, Asep Husni Yasin; Febrianda, Rendi; Hermawati, Wati; Aminullah, Erman (STI Policy and Management Journal, 2023)
This article discusses industrial development on EV di Indonesia, viewed from Sectoral system of innovation (SSI) perspective. The objective of this study is to map challenges in connecting the elements of SSI for developing EV industry. The method of study is a desk research, where the information input relies on secondary sources, consisting of statistical data, official documents and scientific references. This study found eight challenges to develop EV industry. The institutional challenges include: i. fiscal programs are still less effective to promote industrial  collaboration on EV innovation with universities and R&D institutions; ii. Local content target is still difficult to fulfill; iii.  unreadiness of local industry to be involved in the EV supply chain; and iv. Slow consumer response towards EV program incentives. On the knowledge and technology challenges are: i) the quality and standards of EVs from domestic R&D are still inadequate for commercial scale; and ii.  potential investors have not shown adequate interest  in local EV development. The demand challenges are: i. the plan to make Indonesia as EV hub in ASEAN region is far from reality due to lack of investors; and ii. the lack of ECS accessibility is a barrier to the domestic EV market. Keywords: electric vehicle, sectoral system of innovation, institutions, knowledge and technology, demand